Degradação do concreto de uma Estação de Tratamento de Esgoto (ETE) por ácido sulfúrico biogênico - Hoppe Filho, J.; Rheinheimer, B.; Khoe, S. S.; Artigas, L. V.; Sabbag, A. F.; Medeiros, M. H. F. (Revista ALCONPAT, 2014)
At sewage treatment plants, acid attack (and sulfate attack as a secondary consequence) degrades the cement paste, forming ettringite and/or gypsum, causing expansion, cracking and brittleness. The degradation mechanism of concrete in sewage treatment plants also affects the calcium silicate hydrate (C-S-H), reducing the mechanical capacity and service life. The aim of this paper is to present results of the inspection of a sewage treatment plant, which has been operating for about 15 years, where there is noticeable degradation of concrete by a combined acid and sulfate attack. The analysis includes results of a sample collected in the region immediately above the effluent, which had the highest concentration of bacteria and a specimen extracted from the treatment tank slab. Compressive strength of the specimen is consistent with the project, although scanning electron microscopy images and X-ray diffraction identified the formation of gypsum and ettringite within the concrete.Keywords: acid attack; sulphate attack; durability; reinforced concrete.